2002
DOI: 10.1007/s00125-002-0958-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrosomia despite good glycaemic control in Type I diabetic pregnancy; results of a nationwide study in The Netherlands

Abstract: Aims/hypothesis. To investigate the incidence of foetal macrosomia (i.e. birth weight >90th percentile) in a nonselected nationwide cohort of women with Type I (insulin-dependent) diabetes mellitus in The Netherlands and to identify risk indicators predictive for macrosomia. Methods. We conducted a prospective nationwide cohort based survey regarding the outcome of Type I diabetic pregnancy in The Netherlands. Data of 289 women who gave birth to a live singleton infant without major congenital malformations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(75 citation statements)
references
References 19 publications
6
69
0
Order By: Relevance
“…Our results agree with the literature in that a higher third trimester A 1c was predictive of LGA after adjusting for potential confounders [4,5,26,27]. Even though Evers et al found that third trimester A 1c predicted macrosomia, it was a weak predictor that explained less than 5% of the variance [5].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results agree with the literature in that a higher third trimester A 1c was predictive of LGA after adjusting for potential confounders [4,5,26,27]. Even though Evers et al found that third trimester A 1c predicted macrosomia, it was a weak predictor that explained less than 5% of the variance [5].…”
Section: Discussionsupporting
confidence: 90%
“…Even though Evers et al found that third trimester A 1c predicted macrosomia, it was a weak predictor that explained less than 5% of the variance [5]. A recent study by Law et al was able to demonstrate that significantly higher evening glucoses but significantly lower late afternoon glucoses in the third trimester, as recorded by continuous blood glucose monitoring, were associated with LGA neonates [28].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations